2015
DOI: 10.1007/s10853-015-9028-7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influence of particle size and stiffness state of the nanofiller on the mechanical properties of epoxy/clay nanocomposites using a novel shear-stiff nano-mica

Abstract: The mechanical properties of epoxy/clay nanocomposites were investigated in relation to the particle size and shear stiffness state of the dispersed nanoplatelets. The fracture toughness and the underlying toughening mechanisms were thoroughly discussed in detail. For this study, a highly pure synthetic fluorohectorite with large lateral extensions (&3.8 lm) was used and compared to natural montmorillonite characterized by significantly smaller lateral extensions (&400 nm). Moreover, for the synthetic fluorohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…As for the tensile strength (TS), a significant improvement was recorded only at a concentration of 0.2 wt %, whereas at higher mica loadings TS decreased again, thus approaching the original values of bare PET and pullulan-coated PET. This behavior is most likely related to stress concentration points at the sharp tactoid edges, resulting in flaws (i.e., mechanical failures) at the polymer/filler interface, as already observed in poly(methyl methacrylate) (PMMA)/clay [ 27 ], poly(ethylene terephthalate)/mica [ 4 ], and epoxy/clay [ 7 ] nanocomposites.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As for the tensile strength (TS), a significant improvement was recorded only at a concentration of 0.2 wt %, whereas at higher mica loadings TS decreased again, thus approaching the original values of bare PET and pullulan-coated PET. This behavior is most likely related to stress concentration points at the sharp tactoid edges, resulting in flaws (i.e., mechanical failures) at the polymer/filler interface, as already observed in poly(methyl methacrylate) (PMMA)/clay [ 27 ], poly(ethylene terephthalate)/mica [ 4 ], and epoxy/clay [ 7 ] nanocomposites.…”
Section: Resultsmentioning
confidence: 97%
“…For this reason, the use of synthetic NBBs as attractive nanomaterials is rising at both the academic and industrial level. Until now, only a few studies have dealt with the use of mica in nanocomposites, including thermoset and thermoplastic polymers to improve barrier performance [ 3 , 4 ] and mechanical properties [ 2 , 5 , 6 , 7 ]. There is, however, a gap in the literature that this work aims to fill, specifically dealing with advances regarding mica-based biopolymer nanocomposite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The water/oil mass ratio plays an important role in the formation of particles and their characteristics . When the water/oil mass ratio was too low, the cooling and heat transfer capacity of copolymerization system decreased, and the dispersed phase droplets were easy to collide and aggregate, resulting in the formation of larger polymer particles.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in the past that many different factors influence the toughening of neat resin. The most important ones are the size of particles, the aspect ratio, the compatibility of the filler and the matrix, the dispersion quality and the orientation of particles [14,15]. In earlier work we have shown that a high particle diameter and aspect ratio are beneficial for a number of toughening mechanisms [11,16].…”
Section: Introductionmentioning
confidence: 99%